Aluminum phosphate coating talcum powder filler, preparation method and application thereof, and flame-retardant PEO composite material
By using the synergistic effect of aluminum phosphate-coated talc filler and DiDOPO flame retardant in PEO-based materials, the PEO composite material is modified, and the flammability and mechanical properties of PEO-based materials are insufficient, and the flame retardant performance of the material is achieved and significantly improved mechanical properties.
Patent Information
- Application Number
- CN202411541565.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
Polyethylene oxide (PEO)-based materials have limited their development due to their extremely high flammability and poor mechanical properties. The existing improved methods are complex in process and damage the material structure and performance.
Using aluminum phosphate-coated talc powder filler as a multifunctional additive, the talc powder is dispersed in water through the preparation method, adjust the pH value, and add a homogeneous solution of phosphoric acid and aluminum hydroxide to form an aluminum phosphate coating with talc powder as the core. talc filler and use it in conjunction with DiDOPO flame retardant to modify PEO composite material.
Effectively improve the flame retardant properties and mechanical properties of PEO composite materials, realize strong PEO composite materials with low fire hazards under low filler loads, simplify the preparation process and avoid the use of toxic and harmful solvents.
Smart Images

Figure CN119431891A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material modification, and in particular to an aluminum phosphate coated talc filler, a preparation method and application thereof, and a flame retardant PEO composite material. Background Art
[0002] Polyethylene oxide (PEO) is widely used in the fields of synthetic water-soluble films, textile slurries, solid polymer electrolytes for all-solid-state lithium batteries, etc. However, due to the extremely high flammability and poor mechanical properties of PEO-based materials, its development is greatly restricted. Therefore, it is very important to improve the flame retardancy and mechanical properties of PEO-based materials. Although some physical and chemical methods have been developed to improve the flame retardancy and mechanical properties of PEO-based materials, these methods are still complex and will damage their original structure and performance.
[0003] Currently, there are two main methods used to improve the flame retardant properties of polymers. One is to introduce flame retardant elements (such as bromine and phosphorus) into the polymer chain through chemical reactions, and the other is to physically add widely used flame retardant particles to the polymer matrix. For halogen-containing flame retardants, their application is limited because the smoke and toxic gases released after combustion are highly threatening to the environment and humans. In addition, it is difficult to meet the current growing industrial needs using a single flame retardant; therefore, synergistic flame retardant strategies have received increasing attention. In order to meet the above challenges, it is necessary to develop efficient and environmentally friendly flame retardant systems while constructing high-performance PEO composites. Summary of the invention
[0004] In order to solve the above technical problems, an aluminum phosphate coated talc filler and its preparation method and application, and a flame retardant PEO composite material are provided. The present invention uses the aluminum phosphate coated talc filler as a multifunctional additive to modify a polymer, especially to modify PEO, which can effectively improve the flame retardant properties and mechanical properties of the PEO composite material.
[0005] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing an aluminum phosphate coated talc filler, comprising the following steps:
[0007] S1. Dispersing talc in water and adjusting the pH value to below 3.5 to form a talc dispersion;
[0008] S2. Under stirring, dropwise add the prepared homogeneous solution containing phosphoric acid and aluminum hydroxide into the talcum powder dispersion, continue stirring for a period of time after the dropwise addition is completed, and then adjust the pH value of the system to above 4.5;
[0009] S3. Filter out the product, wash it with water, dry it, and calcine it to obtain an aluminum phosphate coated talc filler with a core-shell structure and talc as the core (represented by Talc@AlPO4).
[0010] Furthermore, the mass ratio of the talcum powder, the phosphoric acid, and the aluminum hydroxide is 10:15-18:2-2.5
[0011] Furthermore, the mass concentration of the talc dispersion is 0.05-0.08 g / mL, and the purity of the talc is at least 90 wt %; based on the total amount of phosphoric acid and aluminum hydroxide, the mass concentration of the homogeneous solution is 1.8-2.5 g / mL, wherein the mass fraction of phosphoric acid is at least 85%, and the purity of aluminum hydroxide is at least 99 wt %.
[0012] Further, the required pH value in S1 is adjusted with hydrochloric acid solution, and the required pH value in S2 is adjusted with ammonia solution. Preferably, the required pH value in S1 is adjusted with hydrochloric acid solution to 2.0, and the required pH value in S2 is adjusted with ammonia solution to 5.0.
[0013] Furthermore, the drying is performed at a temperature below 100° C. to a constant weight; and the calcination is performed by heating the mixture to 800-1000° C. in a nitrogen atmosphere and calcining the mixture for 1-3 hours.
[0014] The second aspect of the present invention provides an aluminum phosphate coated talc filler prepared by the above preparation method.
[0015] The third aspect of the present invention provides the use of the aluminum phosphate coated talcum powder filler prepared by the above preparation method in polymer materials. It is used as a multifunctional filler to simultaneously improve the flame retardant properties and mechanical properties of the material, and is used as a synergistic flame retardant in flame retardant modification. The addition percentage in the polymer material is 1wt%-50wt%.
[0016] The fourth aspect of the present invention provides a flame-retardant PEO composite material, in which an aluminum phosphate-coated talc filler is used as a multifunctional additive and a phosphaphenanthrene flame retardant is used as a synergistic flame retardant to jointly modify a PEO substrate to prepare a flame-retardant PEO composite material, wherein the aluminum phosphate-coated talc filler prepared by the above preparation method accounts for 5wt%-15wt%, and the phosphaphenanthrene flame retardant accounts for 5wt%-15wt%.
[0017] Furthermore, the phosphaphenanthrene flame retardant is selected from phenylethyl bridge chain 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DiDOPO).
[0018] Beneficial technical effects:
[0019] The preparation process of the present invention is simple, no toxic or harmful solvents are used, and due to the synergistic effect of the Talc@AlPO4 hybrid material and the DiDOPO flame retardant, the nano-AlPO4 hybrid material is evenly dispersed on the surface of the Talc fiber and has good interfacial compatibility with the PEO matrix. DiDOPO provides high flame retardant efficiency, resulting in a strong PEO composite material with low fire hazard at low filler loading, which can effectively improve the flame retardant and mechanical properties of PEO. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The SEM images of talc powder and aluminum phosphate coated talc powder (Talc@AlPO4) prepared in Example 1; wherein (a) is Talc, and (b) is Talc@AlPO4;
[0021] Figure 2 SEM images of residual carbon of PEO and composite materials PEO / DiDOPO, PEO / DiDOPO / Talc@AlPO45, and PEO / DiDOPO / Talc@AlPO415;
[0022] Among them, (a) is PEO, (b) is PEO / DiDOPO, (c) is PEO / DiDOPO / Talc@AlPO45, and (d) is PEO / DiDOPO / Talc@AlPO415;
[0023] Figure 3 The fracture morphology SEM images of PEO and composite materials PEO / DiDOPO, PEO / DiDOPO / Talc@AlPO45, and PEO / DiDOPO / Talc@AlPO415;
[0024] Among them, (a) is PEO, (b) is PEO / DiDOPO, (c) is PEO / DiDOPO / Talc@AlPO45, and (d) is PEO / DiDOPO / Talc@AlPO415;
[0025] Figure 4 This is a comparison chart of the mechanical properties of samples 1 to 5. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
[0027] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0028] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0029] In the following cases, Talc represents talc, Talc@AlPO4 represents aluminum phosphate coated talc filler, and DiDOPO represents phenethyl bridged 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0030] Example 1
[0031] The preparation method of aluminum phosphate coated talc filler comprises the following steps:
[0032] S1. Prepare Talc dispersion:
[0033] 10 g of dried Talc powder (purity 99 wt%) was completely dispersed in 160 mL of deionized water, and HCl (AR, mass fraction 37 wt%) was added to adjust the pH to 2.0 to form a Talc dispersion;
[0034] S2. Prepare a homogeneous solution containing phosphoric acid and aluminum hydroxide: dissolve 17.33 g H3PO4 (mass fraction ≥ 85 wt%) and 2.33 g Al(OH)3 (purity ≥ 99 wt%) in 10 mL of deionized water under effective stirring to obtain a uniform homogeneous solution;
[0035] Under stirring, the homogeneous solution containing phosphoric acid and aluminum hydroxide prepared above was added dropwise to the Talc dispersion in S1. After the addition was completed, stirring was continued for 30 minutes. Then, the pH value of the system was adjusted to 5.0 with aqueous ammonia (AR, mass fraction 27%).
[0036] S3. Filter out the product and wash it with water several times, dry it at 80°C for 12 hours; then heat it to 900°C in a nitrogen atmosphere and calcine it for 2 hours to obtain a core-shell Talc@AlPO4 hybrid material powder filler with Talc as the core.
[0037] The core-shell Talc@AlPO4 hybrid material powder filler and talc raw material in this case were observed by SEM. The SEM images of talc and Talc@AlPO4 are shown in Figure 1 As shown, (a) is Talc, (b) is Talc@AlPO4, Figure 1 It can be seen that the surface of talc powder has a coating of aluminum phosphate, and the nano-AlPO4 hybrid material is evenly dispersed on the surface of Talc fiber.
[0038] Example 2
[0039] The preparation method of aluminum phosphate coated talc filler comprises the following steps:
[0040] S1. Prepare Talc dispersion:
[0041] 10 g of dried Talc powder (purity 98 wt%) was completely dispersed in 160 mL of deionized water, and HCl (AR, mass fraction 37 wt%) was added to adjust the pH to 2.0 to form a Talc dispersion;
[0042] S2. Prepare a homogeneous solution containing phosphoric acid and aluminum hydroxide: dissolve 17.33 g H3PO4 (mass fraction ≥ 85 wt%) and 2.33 g Al(OH)3 (purity ≥ 99 wt%) in 10 mL of deionized water under effective stirring to obtain a uniform homogeneous solution;
[0043] Under stirring, the homogeneous solution containing phosphoric acid and aluminum hydroxide prepared above was added dropwise to the Talc dispersion in S1. After the addition was completed, stirring was continued for 30 minutes. Then, the pH value of the system was adjusted to 5.0 with aqueous ammonia (AR, mass fraction 27%).
[0044] S3. Filter out the product and wash it with water several times, dry it at 80°C for 12 hours; then heat it to 1000°C in a nitrogen atmosphere and calcine it for 2 hours to obtain a core-shell Talc@AlPO4 hybrid material powder filler with Talc as the core.
[0045] Example 3
[0046] The preparation method of aluminum phosphate coated talc filler comprises the following steps:
[0047] S1. Prepare Talc dispersion:
[0048] 10 g of dried Talc powder (purity 97 wt%) was completely dispersed in 160 mL of deionized water, and HCl (AR, mass fraction 37 wt%) was added to adjust the pH to 2.0 to form a Talc dispersion;
[0049] S2. Prepare a homogeneous solution containing phosphoric acid and aluminum hydroxide: dissolve 17.33 g H3PO4 (mass fraction ≥ 85 wt%) and 2.33 g Al(OH)3 (purity ≥ 99 wt%) in 10 mL of deionized water under effective stirring to obtain a uniform homogeneous solution;
[0050] Under stirring, the homogeneous solution containing phosphoric acid and aluminum hydroxide prepared above was added dropwise to the Talc dispersion in S1. After the addition was completed, stirring was continued for 30 minutes. Then, the pH value of the system was adjusted to 5.0 with aqueous ammonia (AR, mass fraction 27%).
[0051] S3. Filter out the product and wash it with water several times, dry it at 85°C for 12 hours; then heat it to 950°C in a nitrogen atmosphere and calcine it for 2 hours to obtain a core-shell Talc@AlPO4 hybrid material powder filler with Talc as the core.
[0052] Application Examples
[0053] The Talc@AlPO4 hybrid material powder filler prepared in Example 1 was used as a synergistic flame retardant in PEO material to prepare a flame retardant PEO composite material.
[0054] The flame retardant PEO composite material is composed of samples with five ratios as shown in Table 1 below (based on 100% by mass).
[0055] Table 1 Material ratio
[0056]
[0057] Preparation process of the above five samples: weigh the materials according to the above ratios, and before processing, vacuum dry the materials in an oven for 12 hours. After the materials are mixed evenly, use a torque rheometer to melt blend and prepare flame-retardant PEO composite materials. Melt blending process: melt blending at 150°C for 6 minutes, and the screw speed is 50rpm; then use a flat vulcanizer to make samples of suitable sizes, and the corresponding procedure is as follows: hot press the blend at 150°C for 10 minutes, and cold press at 15MPa pressure at room temperature for 15 minutes, and obtain samples of each flame-retardant PEO composite material after cooling.
[0058] The above five kinds of samples were subjected to mechanical property tests (test standard ASTM D638), and the test results are shown in Table 2. Figure 3 and Figure 4 .
[0059] Table 2 Mechanical properties of samples with five ratios
[0060]
[0061]
[0062] From Table 2 and Figure 4 It can be seen that the addition percentage of Talc@AlPO4 in the composite material is 10%-15%, which has a significant improvement on the mechanical properties of the material. The fracture morphology of samples 1, 2, 3, and 5 is shown in Figure 2. Figure 3 As shown in the figure, Talc@AlPO4 is dispersed more evenly in the material. Talc@AlPO4 hybrid material has a synergistic effect with DiDOPO flame retardant. Nano-AlPO4 hybrid material is evenly dispersed on the surface of Talc fiber and has good interface compatibility with PEO matrix, which significantly improves the mechanical properties of the composite material.
[0063] The above five ratios of samples were subjected to thermogravimetric analysis and flame retardant performance tests. The specific results are shown in Table 3 and Figure 2 .
[0064] Table 3 TGA properties and flame retardant properties of samples with five ratios
[0065]
[0066] From Table 3 and Figure 2 It can be seen that PEO is flammable, has a small amount of residual carbon, and the surface of the residue is relatively rough; after adding 12wt% DiDOPO, the amount of residual carbon increases, and the holes and pores on the surface of the residue are reduced; after adding Talc@AlPO4 hybrid, a relatively dense and complete char layer can be formed, which can limit the entry of oxygen into the polymer matrix and further diffusion. The Talc@AlPO4 hybrid with a core-shell structure of the present invention, as a synergistic flame retardant, forms multiple synergistic flame retardant effects with DiDOPO, mainly including gas phase and condensed phase flame retardant effects, which can effectively enhance the flame retardant to improve the performance of the polymer.
[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an aluminum phosphate coated talc filler, characterized in that: The steps include: S1. Dispersing talcum powder in water and adjusting the pH value to below 3.5 to form a talcum powder dispersion; S2. Under stirring, dropwise add the prepared homogeneous solution containing phosphoric acid and aluminum hydroxide into the talcum powder dispersion, continue stirring for a period of time after the dropwise addition is completed, and then adjust the pH value of the system to above 4.5; S3, filtering out the product, washing it with water, drying it, and calcining it to obtain an aluminum phosphate coated talc filler with a core-shell structure and talc as the core.
2. The method for preparing the aluminum phosphate coated talc filler according to claim 1, characterized in that: The mass ratio of the talc powder, the phosphoric acid and the aluminum hydroxide is 10:15-18:2-2.
5.
3. The method for preparing the aluminum phosphate coated talc filler according to claim 2, characterized in that: The mass concentration of the talc dispersion is 0.05-0.08 g / mL, and the purity of the talc is at least 99 wt %; based on the total amount of phosphoric acid and aluminum hydroxide, the mass concentration of the homogeneous solution is 1.8-2.5 g / mL, wherein the mass fraction of phosphoric acid is at least 85%, and the purity of aluminum hydroxide is at least 99 wt %.
4. The method for preparing the aluminum phosphate coated talc filler according to claim 1, characterized in that: The required pH value in S1 is adjusted with hydrochloric acid solution; the required pH value in S2 is adjusted with ammonia solution.
5. The method for preparing the aluminum phosphate coated talc filler according to claim 1, characterized in that: The drying is performed at a temperature below 100° C. to a constant weight; the calcination is performed by heating the mixture to 800-1000° C. in a nitrogen atmosphere and calcining the mixture for 1-3 hours.
6. Aluminum phosphate coated talc filler prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the aluminum phosphate coated talc filler prepared by the preparation method according to any one of claims 1 to 5 in polymer materials, characterized in that: The aluminum phosphate coated talcum powder filler serves as a multifunctional filler and improves both the flame retardant properties and the mechanical properties of the material.
8. The use according to claim 7, characterized in that: The aluminum phosphate coated talcum powder filler is used as a synergistic flame retardant in flame retardant modification, and its addition percentage in the polymer material is 1wt%-50wt%.
9. A flame retardant PEO composite material, characterized in that: The aluminum phosphate coated talc filler prepared by the preparation method according to any one of claims 1 to 5 is used as a multifunctional additive, and the phosphaphenanthrene flame retardant is used as a synergistic flame retardant to jointly modify the PEO substrate, thereby preparing a flame retardant PEO composite material; In the flame-retardant PEO composite material, the aluminum phosphate coated talc filler accounts for 5wt%-15wt%, and the phosphaphenanthrene flame retardant accounts for 5wt%-15wt%.
10. The flame retardant PEO composite material according to claim 9, characterized in that: The phosphaphenanthrene flame retardant is selected from phenylethyl bridge chain 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.